Phosphorylating titin’s cardiac N2B element by ERK2 or CaMKII [delta] lowers the single molecule and cardiac muscle force - Perkin, John; Labeit, Siegfried (Biophysical journal, 2015)
Titin is a large filamentous protein that is responsible for the passive force of the cardiac sarcomere. Titin’s force is generated by its I-band region, which includes the cardiac-specific N2B element. The N2B element consists of three immunoglobulin domains, two small unique sequence insertions, and a large 575-residue unique sequence, the N2B-Us. Posttranslational modifications of the N2B element are thought to regulate passive force, but the underlying mechanisms are unknown. Increased passive-force levels characterize diastolic stiffening in heart-failure patients, and it is critical to understand the underlying molecular mechanisms and identify therapeutic targets. Here, we used single-molecule force spectroscopy to study the mechanical effects of the kinases calcium/calmodulin-dependent protein kinase II delta (CaMKIIδ) and extracellular signal-regulated kinase 2 (ERK2) on the single-molecule mechanics of the N2B element. Both CaMKIIδ and ERK2 were found to phosphorylate the N2B element, and single-molecule force spectroscopy revealed an increase in the persistence length (Lp) of the molecule, indicating that the bending rigidity of the molecule was increased. Experiments performed under oxidizing conditions and with a recombinant N2B element that had a simplified domain composition provided evidence that the Lp increase requires the N2B-Us of the N2B element. Mechanical experiments were also performed on skinned myocardium before and after phosphorylation. The results revealed a large (∼30%) passive force reduction caused by CaMKIIδ and a much smaller (∼6%) reduction caused by ERK2. These findings support the notion that the important kinases ERK2 and CaMKIIδ can alter the passive force of myocytes in the heart (although CaMKIIδ appears to be more potent) during physiological and pathophysiological states.
Gesehen am 19.10.2017